Manajemen SDM dalam Penyelenggaraan Program JKN-KIS: Sebuah Tinjauan Literatur - Syarifuddin Syarifuddin; Chandra Nurcahyo; Andi Afdal (Jurnal Jaminan Kesehatan Nasional, 2021)
The practice of human resource management has developed rapidly. Various figures and experts have explained theories and best practices about HR management in an organization. Employees are no longer considered just a resource that will run out over time. Currently, organizations in various sectors have placed employees as valuable assets that must be managed properly so that they are expected to be able to make an optimal contribution in supporting the achievement of organizational targets. BPJS Kesehatan as the only public legal entity that organizes the National Health Insurance-Indonesian Health Card (JKN-KIS) program is deemed necessary to place the function of HR management as one of the strategic aspects that must be managed optimally. This study aims to provide an overview of the suitability of the implementation of HR management at BPJS Kesehatan with various existing literature references and best practices in companies or other organizations that have succeeded in becoming market leaders in their fields. This study uses a literature study based on references in the form of books and previous research on HR management. An important finding in this study is the implementation of HR management at BPJS Kesehatan is following the HR Four Role Model proposed by Ulrich (1997) which has been recognized as one of the references in HR management practices in organizations.